(untitled) (Nigerian Journal of Technology, 2025)
Soil hydrology plays a crucial role in many fields of study, including agriculture, due to the variation in the length of the rainy season brought about by erratic weather patterns. To mitigate crop failure, sustainable and drought-resistant agricultural techniques must be developed. This can be achieved by comprehending the transformative effects of nanoparticles on soil structure, water availability, and nutrient dynamics. Hence, this study aims to explore the impact of biochar-based nanoparticles on the hydrological properties of agricultural soil. Six (6) levels of biochar-based nanoparticles were used as treatments at 0 g, 100 g, 200 g, 300 g, 400 g, and 0 g with constant water supply as control applied to 20 g of soil. The hydrological properties considered are clay flocculation, dispersion ratio, structural stability, void ratio, sodium percentage, and water retention ability, among others, are relevant to agriculture. Biochar addition initially increased soil moisture retention and soil aggregation, but impaired stability at excessive levels due to nanoparticle toxicity. Clay flocculation dramatically improved with 100 g of biochar nanoparticle, yet severely declined beyond 200 g due to toxicity inhibiting natural aggregation. Lower biochar application rates increased aggregate stability compared to control samples, but stability did not increase proportionately as biochar application increased. Compared to higher amounts, the void ratio significantly changed with 100 g biochar addition, .patterns in stability and sodium content indicate biochar nanoparticles profoundly altered soil structure, highlighting the narrow threshold between benefits and ecosystem damage from excessive application. It was concluded that as much as biochar-based nanoparticles can help improve the hydrological properties of the agricultural soil, application beyond 200 g could have a counter effect and hence has to be monitored.